Development of Industry 4.0 and the Issue of Technological Unemployment Case Study – Poland - Aleksandra KUZIOR (Communications of International Proceedings, 2021)
The article presents the issues of positive and negative effects of the development of Industry 4.0 by referring, among others, to the issue of technological unemployment. The aim of the article is to indicate the need for appropriate education programming, including lifelong learning, aimed at acquiring both professional, engineering and humanistic, ethical and social competences.in order to avoid technological unemployment (defined as temporary, short-term unemployment lasting until human capital is reallocated to other uses) becoming structural unemployment, which is much more dangerous from an economic and social point of view. The article also contains an analysis of the labour market in terms of the demand for specific competences in the view of the development of Industry 4.0 in Poland and presents forecasts regarding the demand for competences of the future and indicates probable future professions. There is no doubt that the development of Industry 4.0 requires specialised competences combining the skills of an IT specialist and an automation/robotics specialist skilled in the integration of cyber-physical systems, the operation of advanced production management systems and complex production data analysis systems, and the application of artificial intelligence algorithms in the production space. Such specialists will be needed in the Polish labour market in the coming years. Professionals with high communication, interpersonal and social skills will also continue to be in demand.
Keywords: Industry 4.0; technological unemployment; competences